Advancements with Controlled-Release Fertilizers for Florida Citrus Production: 1996 -2006 - Thomas A. Obreza; Robert Rouse; Edward A. Hanlon (EDIS)
SL-243, an 11-page fact sheet by T.A. Obreza, R. Rouse, and E.A. Hanlon, advises crop advisers, fertilizer dealers, citrus producers and other parties interested in citrus fertilization practices about the advances in fertilizer technology in the past ten years. Published by the UF Soil and Water Sciences Department, July 2006.